Tryptophan catabolism in Pseudomonas aeruginosa and potential for inter-kingdom relationship. Issue 1 (December 2016) - Bortolotti, Perrine; Hennart, Benjamin; Thieffry, Camille; Jausions, Guillaume; Faure, Emmanuel; Grandjean, Teddy; Thepaut, Marion; Dessein, Rodrigue; Allorge, Delphine; Guery, Benoit; Faure, Karine; Kipnis, Eric; et al.
Abstract Background Pseudomonas aeruginosa (Pa) is a Gram-negative bacteria frequently involved in healthcare-associated pneumonia with poor clinical outcome. To face the announced post-antibiotic era due to increasing resistance and lack of new antibiotics, new treatment strategies have to be developed. Immunomodulation of the host response involved in outcome could be an alternative therapeutic target inPa -induced lung infection. Kynurenines are metabolites resulting from tryptophan catabolism and are known for their immunomodulatory properties.Pa catabolizes tryptophan through the kynurenine pathway. Interestingly, many host cells also possess the kynurenine pathway, whose metabolites are known to control immune system homeostasis. Thus, bacterial metabolites may interfere with the host's immune response. However, the kynurenine pathway inPa, including functional enzymes, types and amounts of secreted metabolites remains poorly known. Using liquid chromatography coupled to mass spectrometry and different strains ofPa, we determined types and levels of metabolites produced byPa ex vivo in growth medium, and the relevance of this production in vivo in a murine model of acute lung injury. Results Ex vivo, Pa secretes clinically relevant kynurenine levels (μM to mM).Pa also secretes kynurenic acid and 3-OH-kynurenine, suggesting that the bacteria possess both a functional kynurenine aminotransferase and kynurenine monooxygenase. The bacterial kynurenine pathway is the major pathway leading to anthranilate production both ex vivo and in vivo. In the absence of the anthranilate pathway, the kynurenine pathway leads to kynurenic acid production. Conclusion Pa produces and secretes several metabolites of the kynurenine pathway. Here, we demonstrate the existence of new metabolic pathways leading to synthesis of bioactive molecules, kynurenic acid and 3-OH-kynurenine inPa . The kynurenine pathway inPa is critical to produce anthranilate, a crucial precursor of somePa virulence factors. Metabolites (anthranilate, kynurenine, kynurenic acid) are produced at sustained levels both ex vivo and in vivo leading to a possible immunomodulatory interplay between bacteria and host. These data may imply that pulmonary infection with bacteria highly expressing the kynurenine pathway enzymes could influence the equilibrium of the host's tryptophan metabolic pathway, known to be involved in the immune response to infection. Further studies are needed to explore the effects of these metabolic changes on the pathophysiology ofPa infection.